Vasile Alecsandri and V. A. Urechia (Confluenţe Bibliologice, 2016)
The article presents Vasile Alecsandri’s 195th Anniversary Birthday and V. A. Urechia’s idea to make a bust dedicated to poet who was born in Bacău.
Keywords: Vasile Alecsandri (1821 - 1890); Vasile Alexandrescu-Urechia (1834-1901)